Analisis Pengaruh Parameter Welding SMAW Penggabungan Perbedaan Material SA-36 dan SA-240 Gr. 304 pada Pengelasan Fillet - Nonov Abdillah; Rizki Aulia Nanda; Amir Amir; Khoirudin Khoirudin (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2026)
In the manufacturing and construction industries, welding is the most common method of joining metals. This study aims to optimize SMAW parameters (welding current and travel speed) for joining dissimilar materials—SA-36 and SA-240 Gr.304—in fillet welds. Steel and stainless steel plates were welded using the SMAW process with DCEP polarity. The joints were made using a 90° fillet weld. Welding currents of 100 A and 110 A were used, with E-309 SFA-5.4 welding wire of 3.2 mm diameter. Macroscopic testing was performed on the cross-section of the specimens. Hardness testing was conducted using a Vickers hardness tester on the base metal, Heat Affected Zone (HAZ), and the weld zone. Specimen N4 exhibited the highest penetration at 110 A and a travel speed of 2 mm/s. Specimen N1 had the smallest HAZ width at 100 A and a travel speed of 2.4 mm/s. The visual parameters of specimen N2 were generally optimal as they minimized welding defects. It was concluded that specimen N2 was the most optimal for macro and hardness tests, with a 110 A setting and a high travel speed.